2014
DOI: 10.3109/0284186x.2014.921724
|View full text |Cite
|
Sign up to set email alerts
|

Survival and prognostic factors in patients treated with stereotactic radiotherapy for brain metastases

Abstract: We identified four prognostic factors related to survival after SRT for brain metastases. The grouping of patients by these factors is useful to determine the level of treatment. We discourage the delivery of SRT to patients with 3-4 unfavourable prognostic factors because of the very short median survival of two months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Unfortunately, the electronic medical record documentation does not adequately provide a rationale for the treatment plan chosen. Factors frequently identified with improved survival, such as age, GPA, and systemic cancer status also did not differ between groups [29-30]. Tumor volume and number of tumors treated were also identified as important prognostic factors [29] which were not significantly different as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the electronic medical record documentation does not adequately provide a rationale for the treatment plan chosen. Factors frequently identified with improved survival, such as age, GPA, and systemic cancer status also did not differ between groups [29-30]. Tumor volume and number of tumors treated were also identified as important prognostic factors [29] which were not significantly different as well.…”
Section: Discussionmentioning
confidence: 99%
“…Factors frequently identified with improved survival, such as age, GPA, and systemic cancer status also did not differ between groups [29-30]. Tumor volume and number of tumors treated were also identified as important prognostic factors [29] which were not significantly different as well. Thus, we cannot determine any patient selection bias for SRS in this retrospective study.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Anshushaug et al (19) also observed that ECOG PS 3/4 was strongly associated with palliative radiotherapy during the last month of life. The impact of performance status as a prognostic factor in patients with brain metastases is well known (20). In a Canadian study, palliative patients with cancer presenting ECOG PS 4 or 3 exhibited a median survival time of 25.5 or 55.0 days, respectively (21).…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have demonstrated the benefit of SRT on local control in brain metastases, either with or without prior resection or whole brain radiation therapy. [5][6][7][8][9][10][11] To minimize side effects and maximize the dose to the tumor, small margins between the clinical target volume and the actual treated volume are chosen, requiring highly accurate treatment delivery. 12,13 However, several uncertainties need to be considered for such treatments: computed tomography (CT) to magnetic resonance imaging registration uncertainties 14 ; contouring, patient setup and treatment delivery uncertainties; and intrafractional patient motion.…”
Section: Introductionmentioning
confidence: 99%